2017
DOI: 10.1017/s000711451700085x
|View full text |Cite|
|
Sign up to set email alerts
|

Synbiotic supplementation and the effects on clinical and metabolic responses in patients with rheumatoid arthritis: a randomised, double-blind, placebo-controlled trial

Abstract: Synbiotic intake may be associated with reduced inflammation in patients with rheumatoid arthritis (RA) due to optimised inflammatory markers, oxidative stress and insulin resistance. This research was conducted to assess the effects of synbiotic supplementation on the clinical and metabolic parameters of patients with RA. A total of fifty-four patients with RA were allocated into two groups to receive either a synbiotic capsule (n 27) or a placebo (n 27) for 8 weeks in this randomised, double-blind, placebo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…Probiotic therapy has also been described in RA individuals. Synbiotic capsule supplements with Lactobacillus acidophilus, Lactobacillus casei, and Bifidobacterium bifidum, for example, improved DAS-28 and VAS pain and increased nitrite, an indirect marker of ⋅ NO concentrations, and the GSH in plasma [62]. However, probiotic supplementation containing only Lactobacillus casei was not enough to induce significant effect on oxidative stress indices and antioxidant status in such patients [28].…”
Section: Antioxidant Therapy In Rheumatoid Arthritismentioning
confidence: 97%
See 2 more Smart Citations
“…Probiotic therapy has also been described in RA individuals. Synbiotic capsule supplements with Lactobacillus acidophilus, Lactobacillus casei, and Bifidobacterium bifidum, for example, improved DAS-28 and VAS pain and increased nitrite, an indirect marker of ⋅ NO concentrations, and the GSH in plasma [62]. However, probiotic supplementation containing only Lactobacillus casei was not enough to induce significant effect on oxidative stress indices and antioxidant status in such patients [28].…”
Section: Antioxidant Therapy In Rheumatoid Arthritismentioning
confidence: 97%
“…RA: rheumatoid arthritis. 4 Oxidative Medicine and Cellular Longevity critical contributor in the initiation and maintenance of pathogenic mechanisms observed in systemic inflammatory conditions, including RA [12,19,29,33,34,61,62]. When it comes to physiological conditions, the production and clearance of ROS and RNS should be maintained, ideally, in a dynamic balance, once they exert pleiotropic effects on growth, differentiation, chemotaxis, and cell death [15], being also crucial in the defense mechanisms against pathogens [14].…”
Section: Back In Time: What History Tells Us About the Binomialmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, probiotic use in RA showed controversial results, which could be explained by the use of different bacterial strains [35]. A recent randomized placebo-controlled trial showed that the association of Lactobacillus acidophilus, Lactobacillus casei and Bifidobacterium bifidum probiotics with fiber supplement could significantly decrease disease activity [36].…”
Section: Is Diet a Possible Concomitant Dmard In Ra?mentioning
confidence: 99%
“…Of the 154 articles that were reviewed, a final 12 studies met inclusion criteria and were obtained in full form. [218][219][220][221][222][223][224][225][226][227][228][229] Of these, ten were randomised controlled trials of which nine employed a placebo control methodology and one compared to standard treatment. Two articles were quasiexperimental and only one of these employed a placebo.…”
Section: Study Selectionmentioning
confidence: 99%